Urinary excretion patterns and potential risks of beta‐blocker ophthalmic drops in sports. Issue 1 (1st November 2022) - Lin, Yi‐An; Chiang, Wei‐Yu; Chang, William Chih‐Wei; Kuo, Ming‐Tse; Chen, Alexander; Hsu, Mei‐Chich
Abstract: Beta‐blockers have been prohibited by the World Anti‐Doping Agency (WADA) in certain sports, but insufficient research data make it difficult to distinguish between therapeutic uses or misuses. This study aimed at investigating the urinary excretion pattern following beta‐blocker ophthalmic drops and the potential risk of constituting an adverse analytical finding (AAF) in sports. Prescribed timolol and carteolol ophthalmic drops were used in healthy participants and glaucoma patients. The urine samples were then collected to investigate the urinary excretion pattern following acute and chronic administration of the above beta‐blocker ophthalmic drops. The liquid chromatograph‐tandem mass spectrometry method was applied for measuring urinary beta‐blockers. Our results demonstrated that the levels of both urinary timolol and carteolol exceeded the minimum reporting levels (MRL) following acute and chronic administration. The highest levels of urinary timolol and carteolol observed in the present study were 255.7 and 923.8 ng/ml, respectively. Regarding the acute administration of timolol ophthalmic drop, 26.19 (11/42) of urine samples were detected with timolol higher than the MRL in timed and random sampling. In contrast, the acute administration of carteolol ophthalmic drops made the carteolol levels higher than the MRL among most urine samples. On the other hand, 36.36% (4/11) of urine samples were detected with beta‐blockers higher than the MRL during the chronic administration of timolol and carteolol ophthalmic drops. In the context of receiving ophthalmic beta‐blocker medications, the present study has highlighted the potential risk of constituting an AAF in specific sports and suggests strengthening athletes' awareness of therapeutic use exemptions. Abstract : Although beta‐blockers have been prohibited in certain sports, limited research data are available for distinguishing therapeutic uses or misuses. This study aimed at investigating the urinary excretion pattern following beta‐blocker ophthalmic drops and the potential risk of constituting an adverse analytical finding in sports. Our results displayed both timolol and carteolol ophthalmic drops, following either acute or chronic administration, may induce urinary beta‐blocker levels higher than the minimum reporting level.